2011
DOI: 10.1177/147323001103900448
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Knee Lipoma Arborescens Combined with Osteoarthritis in Elderly Patients

Abstract: Here, three cases of combined lipoma arborescens (LA)--a rare neoplastic lesion of the synovium--and osteoarthritis (OA) with bilateral knee involvement in elderly patients are reported. The clinical, magnetic resonance imaging and histological characteristics of this rare condition are described. Limited by the similarity of symptoms between LA and OA and the low sensitivity of X-ray for discerning LA, it was found that a diagnosis of LA could be easily missed. Follow-up data suggested that the treatment of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…An association between LA and OA has been postulated [ 14 , 23 ], but the causal relationship between these two entities has not been fully clarified. It has been suggested that the long-standing synovial thickening effusions caused by repeated mechanical injury to the proliferated villi eventually lead to OA [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…An association between LA and OA has been postulated [ 14 , 23 ], but the causal relationship between these two entities has not been fully clarified. It has been suggested that the long-standing synovial thickening effusions caused by repeated mechanical injury to the proliferated villi eventually lead to OA [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although SL mostly have unilateral involvement, some reports have shown bilateral involvement of the knee. 18,19 In our study, there was no bilateral involvement. In general, SL affects adults in later life, although some cases involving younger patients have been reported.…”
Section: Discussionmentioning
confidence: 41%
“…Xiao et al had hypothesised that there is synovial proliferation due to inflammation induced by osteoarthritis and subsequently adipose differentiation of the hypertrophied synovium. 11 Al ismail et al 12 and Hubscher et al 13 had also proposed inflammation and mechanical factors in etiopathogenesis of osteoarthritis secondary to lipoma arborescens. Rao et al 14 had proposed that LA could result from inappropriate fat deposition and degenerative disease of the joints.…”
Section: Discussionmentioning
confidence: 99%